Assessment of disease burden and mortality attributable to air pollutants in northwestern Iran using the AirQ+ software - Pegah Nakhjirgan; Ahmad Jonidi Jafari; Majid Kermani; Abbas Shahsavani; Zahra Kazemi; Zohre Kazemi; Farzad Fanaei (Scientific Reports)
Abstract It is well known that one of the main causes of mortality and reduced life expectancy is air pollution, which carries the highest burden of diseases attributed to environmental factors. The poor air quality in Iranian cities leads to a wide range of acute and chronic health effects. This study estimates the natural deaths, ALRI, COPD, lung cancer, IHD, and strokes caused by air pollutants in Bukan, a southern city in West Azerbaijan Province, from 2011 to 2019. Population data was obtained from government organizations, and pollutant data for 2011–2019 was collected from the Bukan Environmental Protection Organization. Analyses were performed using Excel, and the data was subsequently entered into the WHO’s AirQ+ model to extract the results. The study found that long-term exposure to PM10, PM2.5, NO2, and O3 resulted in an estimated 316, 241, 14, and 52 deaths, respectively. By comparing the air quality over the 8-year period, it was determined that the air quality in Bukan city is not in good condition, with particulate matter levels exceeding relevant standards. Given the increasing trend of air pollution and associated health impacts, it is essential to implement effective control policies to improve the city’s air quality. This information provides a crucial step for city managers, policymakers, and health officials to mitigate the health effects caused by air pollution.